Lifelong learning in developing knowledge workers - Abdul Majid, Abdul Halim; Seth, Nor Bizura (UUM Press, 2012)
This monograph discusses the importance of lifelong learning in developing knowledge workers and human capital. Facets of lifelong learning, knowledge workers and human capital are highlighted to provide basic understanding to all readers. The facets of lifelong learning include accessibility to learning, investment for learning, methods and contents of learning, values of learning, direction and guidance in learning and learning opportunities closer to home.Meanwhile, the facets of knowledge worker are problem solving, using intellectual skills, requiring a high level of autonomy, emphasizing on quality of judgment, using unique processes, possessing un-codified knowledge,sourcing between his ears and using knowledge and information to add to deeper knowledge and information.